Development of educational practices in the fi eld of citizenship skills (2019)
This research summary describes educational practices around the citizenship skills, which are developed by eight teachers of the Ramon Martinez Benítez educational institution in the municipality of Cartago, as well as their degree of rapprochement and assimilation on the topic. This paper is also based on a qualitative research through a phenomenological design and an in-depth interview. Besides, there is also an addressedapproach through the analysis of three categories: educational practices, the relationship teacher-student, and citizenship competences; the latter, transversalising the whole investigation. Regarding the fi ndings, there is a presence of emerging categories such as personal and social developmentthrough the formation of values and citizenship, which imply recognition as subjects of rights, as well as the emotional competencies as a transformative element for coexistence, the dialogue and conciliation as a strategy, and the educational practice for citizenship skills as an end.